Математична модель періодично-неоднорідної діелектричної структури - Гоблик, В.В.; Ничай, І.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
Task of research of spatial field distribution which becomes excited by a source over a periodically nonuniform dielectric plate and features of wave processes which are supported by such structure are considered. Mathematical model approach of periodically nonuniform dielectric structure, is presented. Research of influence of dielectric plate on the field of filament of current is carried out. Program for research of dielectric plate properties is got.